Stem Cells for Cancer and Genetic Disease Treatment (Stem Cells in Clinical Applications,, 2018)
This invaluable resource discusses insights ranging from basic biological mechanisms of various types of stem cells through the potential applications in the treatment of human diseases, including cancer and genetic disorders. These discoveries are placed within the structural context of tissue and developmental biology in sections dealing with recent advances in understanding different types of stem cell biology and their potential applications in tissue repair and regeneration and in the treatment different types of human cancer and genetic diseases or disorders. Stem Cells for Cancer and Genetic Disease Treatment and the other books in the Stem Cells in Clinical Applications series will be invaluable to scientists, researchers, advanced students and clinicians working in stem cells, regenerative medicine or tissue engineering as well as cancer or genetics research.